Shale gas in coal country: Testing the Goldilocks Zone of energy impacts in the western Appalachian range. (September 2019) - Junod, Anne N.; Jacquet, Jeffrey B.
Abstract: Impacts from energy development have been shown to affect different demographic, stakeholder, and community groups in different ways, which in turn may differ across energy regimes, project lifecycles, and geographies. This research examines the social and structural influences which may amplify or attenuate the varied impacts of unconventional oil and gas development (UOGD) in a heretofore under-examined energy impact geography: the periphery region of Ohio's Utica Shale. We conduct fifty-four (54) interviews in five Ohio communities to test and extend the Goldilocks Zone analytic framework of energy impacts, in which some energy periphery communities have been shown to experience moderate, positive spillover economic gains but minimal social harms in virtue of their socio-geographic distance from core UOGD activity. We find support for a Goldilocks Zone in the Utica Shale periphery, however the size and strength of effects are attenuated by the varied population densities, geographic and political economy diversities, natural resource legacies, and industry mixes and dependences of the Appalachian Range. This research contributes to the limited scholarship examining the effects of energy development in periphery impact geographies as well as provides baseline energy impact and perception data in a region that has received very little academic scrutiny despite ongoing and significant future potential for unconventional oil and gas development. Finally, this article tests and extends the Goldilocks Zone of energy impacts analytic framework in a new social, geographic, and energy context.